A comparative research between Generation Y and Generation Z in Malacca about the effects of branding on food product sauce “NUR” / Nur Aiyani Fakhira Noor Azmi - Noor Azmi, Nur Aiyani Fakhira (2023)
The chosen branding strategy (including the branding as its integral parts) is highly important in this process. Nowadays, the brand becomes one of the basic motives for the consumers’ choice of a particular food product. The importance of the product brand shall be seen primarily in its impact on consumers’ choice and their loyalty through identifying and differentiating quality and origin, as well as creating additional values. The aim of this paper is to research the extent to which the consumer perceives the brand and how much it affects the evaluation of the functional characteristics of the product, primarily product quality. This paper analyzes the sales of sauces (NUR) as well as explores the effect of the product brand on sales. The main conclusions of the paper are that consumers do not value products based exclusively on their physical characteristics and that in the process of making a purchasing decision when choosing an alternative, consumers will first perceive the brand as “a sign of quality” and then other evaluation criteria (physical appearance and packaging, price, the reputation of the retail network).